An Analytical Study of Cultural Intermediaries through the Select Tales of the Mahabharata - Malhotra, Nitin (International Journal of Psychosocial Rehabilitation, 2020)
Since the emergence of language, humans have been indulged in learning and developing the art of narrating a social or public event either in order to amuse or to be didactic. In the history of Indian literature, epics like the Mahabharata and Ramayana were composed to convey the real teachings of the Vedas and Upanishads to the common people in a comparatively simplified language. The telling and re-telling of the tales embedded in these texts depend upon the prevailing language of people and the system of understanding. We help ourselves to derive new meanings through culturally oriented texts, especially the epics, as they are replete with stories from our origin, life, and death. As Collins Dictionary defines ‘culture’ as a ‘particular society or civilization, especially considered in relation to its beliefs, way of life, or art.’ It is important to understand that art, which is being explored in the Mahabharata, is an integral part of life through which we understand the basis of human life. Cultural intermediaries were the tastemakers who developed the knowledge and contributed to the attitude of life that resulted in a ‘thinking society.’ This research paper attempts to answer the questions about the universal impact of the cultural elements as presented in the tales of the Mahabharata, which is a worldwide acclaimed piece of literature. It also presents the expression of people’s lives and living and cultural understanding at a universal level.